GROWING OF CONTAINERIZED OAK SEEDLINGS USING SUBSTRATES OF DIFFERENT COMPOSITION - Gupal, V. V. (Forestry and Forest Melioration, 2018)
Introduction In industrialized countries, cultivation technologies for containerized planting stock of tree species and establishment of forest plantations with its use are widespread. Today, interest in this planting stock is growing in Ukraine. A choice of a substrate has a great importance for growing the seedlings to ensure better growth in the container. The aim of the research is to determine the efficient composition of container substrates for a cultivation of oak planting stock and to explore the survival rate of containerized seedlings on the planting area. Materials and Methods In the URIFFM, experiments on growing containerized oak seedlings are laid since 2007 on greenhouse complex in Pivdenne Forestry of Kharkiv Forest Research Station. During the experiments, cylindrical individual containers were used which have a close-meshed polymeric material (agrotextile) shell with a density of 30 g?m-2. Container dimensions were as follows: height – 30 cm, diameter – 8 cm, volume – 1,400 cm3. Containers were filled with a different substrate made of ratio sifted mixture of soil, transition milled peat and different wood species sawdust. Variants of the experiment: soil + peat (2:1); soil + peat (3:1); soil + peat + sawdust (1:1:1); soil + sawdust (2:1); soil + sawdust (3:1); soil (control) Each container was filled with a substrate and seeded with one germinated acorn. There were 100 containers in each version of the experiment. After planting acorns containers watering was conducted daily, water consumption norm is 2.5-3.0 l?m-2. Acorns germination and growth dynamics of seedlings have been registered. Results During the seedlings growing on the substrate of forest soil, the germination of acorns was 72 %. In experimental variants, this index increased on average by 12%. It was the smallest in the variant of “soil + peat + sawdust (1:1:1)” substrate and amounted to 75%, or 104% compared to the control. The biggest difference with the control was recorded in “soil + sawdust (2:1)” variant: acorns germination is 86 % or 119 % compared to control. In June, measurements of seedlings heights and diameters were made. In the control, the seedlings biometric parameters were: average height was 14.3 ± 0.32 cm and the average diameter of the root collar was 3.0 ± 0.10 mm. On the “soil + peat (2:1)” substrate the average height was 17.9 ± 0.41 cm, and the diameter of the root collar – 3,6 ± 0,06 mm, which exceeds the values of control by 25 and 20 %, respectively. In July, in the Pivdenne Forestry of Kharkiv Forest Research Station of URIFFM, oak plantations were created using the container-grown planting stock. In autumn, a survival rate of the experimental plants was 91–98 %. The highest rate of survival was in the variant with “soil + peat (2:1)” substrate and exceeded the control by 7 %. Conclusions It was established that the formation of the substrate with soil and peat (2:1) had the largest acorns germination rate (82 %), which is 14 % higher than this value in the control. Seedlings on this substrate greatly exceeded control on biometrics also. Thus, the height of seedlings prevailed by the control on 25 %, and by diameter of the root collar on 20 %. 2. Planting stock survival on forest plantations was very high (91–98 %) in this experiment. The highest survival rate was found in the variant with “soil + peat (2:1)” substrate, which is proposed for further use for growing oak seedlings in containers. It is planned to expand the experiments to intensify the cultivation of containerized oak planting stock with the use of plant growth regulators, fertilizers, absorbents, etc.